EVALUATION OF SHEAR BOND STRENGTH OF COMPOSITE TO DENTIN REWETTED WITH A DESENSITIZER- AN IN-VITRO STUDY - Balagopal, Dr. Sundaresan; Hemasathya, Dr. Bahavathi Ananthan; Gayathri, Dr. Ramasamy Saravanan Saravanan; Sebatni, Dr. M. Anisha Anisha; Navabharathy, Dr. Vasudevan (Journal of Biomedical and Pharmaceutical Research, 2019)
Aim: The aim of the study was to evaluate the shear bond strength of composite to dentin with 2 different dentin bonding agents after dry dentin is rewetted with a desensitizer. Materials and Methods: Sixty human mandibular molars were taken and the occlusal surface was ground to expose flat dentinal surface. The samples were divided into two major groups Group I and Group II based on the bonding agent used. In Group I Gluma Bond5 was used and in Group II Adper Single Bond 2 was used. Each major group is subdivided into three subgroups a, b and c with ten samples each. Sub Group ‘a’ is moist dentin group. Sub Group ‘b’ is dry dentin group, Sub Group ‘c’ is rewetted dentin group. The desensitizer used is GLUMA Desensitizer. All these samples were thermocycled and the shear bond test was performed using Instron Universal Testing Machine. Results: Dry dentin rewetted with GLUMA Desensitizer followed by GLUMA Bond5 showed highest shear bond strength than that of other subgroups. The data was analysed using ANOVA and Tukeys honestly significant test. Conclusion: Desensitizer used as a rewetting agent increases the shear bond strength of composite on dry dentin. Keywords: Glutaraldehyde, rewetting.